Pembinaan Tata Kelola dan Motivasi untuk Pemberdayaan Desa Blimbingsari sebagai Desa Wisata - Putu Ayu Anggya Agustina; Ni Putu Meri Dewi Pendit; Agus Tatang Sopandi; Kadek Masakazu; Wayan Meter (Jurnal SOLMA, 2023)
Background: Blimbingsari Village has a unique spatial layout that is orderly and free from waste, but the community has not been able to take advantage of this uniqueness as a tourist attraction. In addition to the uniqueness possessed by the village, there is potential that has not been fully developed by the community. These potentials include the cultivation of honey, snacks, nuts for the reason that (1) some people do not have entrepreneurial knowledge, and (2) village governments also lack understanding of tourism science. This goal is to optimize village management and increase entrepreneurial motivation through service programs. Method: This service will be carried out in Blimbingsari Village, Jembrana Regency, Bali in April 2023. This service invited 15 village officials and 15 people who owned and did not have businesses. This activity uses data collection methods with interviews, observations, and documentation. Results: (1) Blimbingsari Village Apparatus increased knowledge about tourism villages through tourism resource persons, (2) village communities received entrepreneurial motivation after discussing with entrepreneur resource persons. The novelty is to provide new insights and information about the 3A Concept, namely attractions, amenities, and accessibility as a solution to optimize village management. Conclusion: The realization of an optimal tourism village needs to have an attraction that begins with fostering village apparatus to create identity and create business opportunities by motivating the community.